The Trustworthiness of the Bureau of Labor's Index Number of Wages - Mitchell, Wesley C. (Quarterly Journal of Economics, 1911)
Journal Article The Trustworthiness of the Bureau of Labor's Index Number of Wages Get access Wesley C. Mitchell Wesley C. Mitchell University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 25, Issue 3, May 1911, Pages 613–620, https://doi.org/10.2307/1883618 Published: 01 May 1911